2005
DOI: 10.1074/jbc.m504778200
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Oligomeric Matrix Protein/Thrombospondin 5 Supports Chondrocyte Attachment through Interaction with Integrins

Abstract: Cartilage oligomeric matrix protein/thrombospondin 5 (COMP/ TSP5) is a major component of the extracellular matrix of the musculoskeletal system. Although COMP/TSP5 abnormalities are associated with several pathological conditions, its normal function remains unclear. This study was undertaken to delineate the function(s) of COMP/TSP5 in cartilage, especially regarding its interaction with chondrocytes. We show that COMP/TSP5 can support chondrocyte attachment and that the RGD sequence in COMP/ TSP5 and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
125
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 56 publications
3
125
0
1
Order By: Relevance
“…This observation suggests that different pathways lead to reduced viability, one presumably depending on the unfolded protein response induced by retained proteins (14,16,19), another on extracellular mechanisms, possibly involving altered chondrocyte-matrix interactions, as demonstrated here by impaired cell attachment of primary chondrocytes to mutant COMP variants. It has been shown that chondrocytes bind to COMP through receptors of the integrin family (47) and that integrin-mediated interactions with collagen II are important for chondrocyte survival (48 -50). It is conceivable that either an altered binding of COMP to integrin receptors or the COMP-mediated disruption of the extracellular matrix may induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that different pathways lead to reduced viability, one presumably depending on the unfolded protein response induced by retained proteins (14,16,19), another on extracellular mechanisms, possibly involving altered chondrocyte-matrix interactions, as demonstrated here by impaired cell attachment of primary chondrocytes to mutant COMP variants. It has been shown that chondrocytes bind to COMP through receptors of the integrin family (47) and that integrin-mediated interactions with collagen II are important for chondrocyte survival (48 -50). It is conceivable that either an altered binding of COMP to integrin receptors or the COMP-mediated disruption of the extracellular matrix may induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…COMP is a major component of the extracellular matrix of the musculoskeletal system that mediates chondrocyte attachment through interactions with integrins (28). The amount of COMP present in the serum of animals treated with vehicle or PPI-2458 was measured at the conclusion of the treatment.…”
Section: Ppi-2458-induced Inhibition Of Bone Resorption and Cartilagementioning
confidence: 99%
“…22 Binding experiments demonstrate that TSP5 interacts with types I, II and IX collagens, MATN3, aggrecan, granulin-epithelin precursor, and integrins. [22][23][24][25][26][27][28] The presence of an ordered intracellular matrix network in pseudoachondroplasia chondrocytes and colocalization of these proteins in the normal ECM suggest that TSP5 has a significant role in the ECM. 20 These observations support a model in which TSP5, type IX collagen, and MATN3 interact and function to establish and maintain the homeostasis of the ECM.…”
mentioning
confidence: 99%